Resistance to spindle inhibitors in glioblastoma depends on STAT3 and therapy induced senescence - Natanael Zarco; Athanassios Dovas; Virginea de Araujo Farias; Naveen K.H. Nagaiah; Ashley Haddock; Peter A. Sims; Dolores Hambardzumyan; Christian T. Meyer; Peter Canoll; Steven S. Rosenfeld; Rajappa S. Kenchappa (iScience)
Summary: While mitotic spindle inhibitors specifically kill proliferating tumor cells without the toxicities of microtubule poisons, resistance has limited their clinical utility. Treating glioblastomas with the spindle inhibitors ispinesib, alisertib, or volasertib creates a subpopulation of therapy induced senescent cells that resist these drugs by relying upon the anti-apoptotic and metabolic effects of activated STAT3. Furthermore, these senescent cells expand the repertoire of cells resistant to these drugs by secreting an array of factors, including TGFβ, which induce proliferating cells to exit mitosis and become quiescent—a state that also resists spindle inhibitors. Targeting STAT3 restores sensitivity to each of these drugs by depleting the senescent subpopulation and inducing quiescent cells to enter the mitotic cycle. These results support a therapeutic strategy of targeting STAT3-dependent therapy-induced senescence to enhance the efficacy of spindle inhibitors for the treatment of glioblastoma.